Geo-Chicago 2016 : geotechnics for sustainable energy : selected papers from sessions of Geo-Chicago 2016, August 14-18, 2016, Chicago, Illinois - Yesiller, Nazli; Zekkos, Dimitrios; Farid, Arvin; De, Anirban; Reddy, Krishna R. (American Society of Civil Engineers, 2016)
Contains 67 peer-reviewed papers on innovative ways of storing and extracting energy in and from geotechnical media and structures. Topics include: thermal geotechnics; geoenergy; mining wastes; energy geotechnics; offshore energy geotechnics; renewable energy; numerical and experimental modeling; and sustainable pavement solutions.
Sponsored by Geo-Institute of the American Society of Civil Engineers.
Keywords: Environmental geotechnology -- Congresses.; Geothermal engineering -- Congresses.; Geothermal resources -- Congresses.; Soils -- Thermal properties -- Congresses.; Heat -- Transmission -- Congresses.; Offshore structures -- Congresses.; Mineral industries -- Waste disposal -- Congresses.; Pavements, Asphalt -- Recycling -- Congresses.; elektronické knihy; electronic books